OxWalk: Wrist and hip-based activity tracker dataset for free-living step detection and gait recognition - Small, S R; von Fritsch, L; Doherty, A; Khalid, S; Price, A (University of Oxford, 2022)
This dataset contains Axivity AX3 activity tracker (accelerometer) data collected from 39 participants in 2019-2020 around the Oxfordshire area. Calibrated and resampled traxial acceleration data is included, captured during unscripted, free living in healthy adult volunteers (aged 18 and above) with no lower limb injury within the previous 6 months and who were able to walk without an assistive device. Participants wore four triaxial accelerometers concurrently (AX3, Axivity, Newcastle, UK), two placed side-by-side on the dominant wrist and two clipped to the dominant-side hip at the midsagittal plane. Accelerometers were synchronised using the Open Movement GUI software (v.1.0.0.42), with one recording at 100 Hz and the other at 25 Hz at each body location. Foot-facing video was captured using an action camera (Action Camera CT9500, Crosstour, Shenzhen, China) mounted at the participant’s beltline. From the synchronised camera data, a step is annotated in each CSV file by a single "1" at the approximate time of heel strike.